A influence between Store Atmosphere and Product Diversity on Customer Loyalty through Purchasing Decisions City: The research location is in Malang City - samboro, joko; Hadi, Musthofa; Maskan, M.; Helmy, Abdullah; Arjo, Tri Ramadani; Iqbal, Muhammad (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
The main objective of this research is: to determine and analyze the significant influence between Store Atmosphere and Product Diversity on Customer Loyalty through Purchasing Decisions. The research location is in Malang City, while the population of this research is all buyers at Miniso MOG stores while the sample is 100 respondents.  The research results show that not all data used is valid and reliable; The better the Store Atmosphere and Product Diversity, the higher the Purchasing Decision; The better the Store Atmosphere and Product Diversity, the higher the Purchase Decision, the stronger the Customer Loyalty; The total influence of the variables studied is 13.52%.